An investigation of causes of conflict men and women officers working at the General Directorate of Sports - Murat Sentuna (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to determine the causes of conflict male and female civil servants working in theGeneral Directorate of Sports (GDS). In this study, between the ages of 20 to 55 different positions in differentdepartments and employees participated in 44 male 33 female officers. 1-20 years of work of the officers, and 42participants were married, 33 were single. In the study, Conflict Assessment Questionnaire consisting of 18questions was used. In addition to age, gender, marital status and year of work were asked demographicinformation. The information obtained in the tables was arranged. Moreover chi-square test in 0.05 level wasapplied in order to understand whether there was a difference between answers. As a result of statisticalcomparisons, the answers given to the participants age, marital status, gender, and year of work according to thelevel of significance of the differences observed (p lt;0,05). As a result, the working parts of the participants isunable to communicate due to the reason of the conflict, the top authorities to take into account wishes of thestaff and subordinates for keeping under constant control of the working environment was originated.